Being and Nothingness of COVID-19 in Nigeria: A Case of Excessive Propaganda and Misplaced Political Economy - NWANEGBO-BEN, John; OZOIGBO, Bonaventure I (Socialscientia: Journal of Social Sciences and Humanities, 2021)
The ontological character of COVID-19 as a pandemic in Nigeria is bizarre and interesting when viewed from the Nigerian perspective. The being of COVID-19 as a disease cannot be contested, and its claimed magnitude cannot be determined or ascertained in Nigeria. The claimed rise, prevention and control In Nigeria as propagated on our media can be viewed with mixed feelings. It is a fact from all scientific investigation and research that there exists a pandemic of this nature worldwide, but when we analyze the political economy of COVID-19 in Nigeria, we may begin to wonder the distinction between Being and nothingness of the disease in Nigeria. We may be forced to begin to wonder the role of propaganda in this “pandemic” Our approach shall be descriptive and analytic. The questions that may be asked are, what actually is the pandemic? Is it the phobia or the disease itself? This is critical when analyzed from those who had practical experiences of the disease and survived or their loved ones survived or died in it. In addition are those who have neither of the above but died from the vicious propaganda and side effect of it. The objective of this paper emphatically posits that the being of COVID-19 in Nigeria when compared to other diseases is nothing but excessive propaganda motivated by misplaced political economy.